Sporolithon tenue sp. nov. (Sporolithales, Corallinophycidae, Rhodophyta): A new rhodolith‐forming species from the tropical southwestern Atlantic. Issue 1 (14th November 2013) - Bahia, Ricardo G.; Amado‐Filho, Gilberto M.; Maneveldt, Gavin W.; Adey, Walter H.; Johnson, Gabriel; Marins, Bianca V.; Longo, Leila L.
Summary A new species conforming to the generic description of Sporolithon was found forming small (1–3 cm in diameter) rhodoliths at 18–75 m depth on the eastern coast of Brazil. Sporolithon tenue Bahia, Amado‐Filho, Maneveldt et W.H. Adey, sp. nov. differs from other species of Sporolithon in having a thin, primary vegetative thallus of only 45–250 μm in thickness composed of up to 20 cell layers. Sporolithon tenue can build thicker crusts by overgrowths of thalli with new hypothallia. The absence of a layer of elongate cells at the base of the tetrasporangial chambers and the shedding of senescent tetrasporangial sori are also characters that separate the new species from all other currently recognized species within the genus. Observations from recently collected material and from herbarium specimens show that specimens previously designated as Sporolithon africanum (Foslie) J. Afonso‐Carillo in Brazil correspond to Sporolithon tenue. Molecular phylogenetic analyses of psbA sequence alignments show that the new species is phylogenetically distinct within the genus Sporolithon.